Bank Rabbna: Islamic Digital Banking for Sustainable Growth and Socioeconomic Development - Shalaby, Ahmed (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: This study reports a 15-year longitudinal case conducted at the Human Information Technology Laboratory in Finland, addressing persistent challenges in achieving sustainable economic growth amid rapid digital transformation and FinTech Development. Objective: This research aims to examine the feasibility of creating sustainable growth through a novel digital banking technology that integrates technological innovation, socioeconomic Development, and ethical principles aligned with the Sustainable Development Goals. Method: This study employs a qualitative, longitudinal case study approach. Data were derived from real-world experimentation and product Development (2008–2023), including multiple innovation projects such as Maestro and Bank Rabbna, with an emphasis on practical implementation over theoretical simulation. Result: The findings indicate that conventional economic growth models face structural paradoxes, particularly between financial market expansion and real economic sustainability. The study formulates Sustainable Growth Theory (SGT), Growth Sustainability Key Performance Indicators (GSKPIs), and the Sustainable State Model (SSM) as integrative solutions. Bank Rabbna is a concrete digital banking application that operationalizes these frameworks by integrating FinTech innovation with Islamic finance principles. Implication: This suggests that combining planning, implementation, and evaluation within a unified digital ecosystem can support balanced and inclusive socioeconomic growth, positioning digital banking as a strategic tool for sustainable Development.